Apokaliptik Resistan: Dialog Moltmann dan Žižek serta Relevansinya di Masa Pandemi - John C. Simon (Veritas : Jurnal Teologi dan Pelayanan, 2022)
How to understand apocalyptic in the current COVID-19 pandemic? This is the question as well as the significance of the problem to be answered. Is it based on Jürgen Moltmann’s theological opinion through his “adventus” and emphasizes divine transcendence, or based on Slavoj Žižek’s opinion, which is “Christian materialism,” which rejects divine transcendence? By using a comparative-analytical method and qualitative research, this paper aims to find meaning that is found through the encounter between Moltmann’s idea of adventus and Zižek’s suggestion to build a new community through “resistance.” The result is that the COVID-19 pandemic is a resistant apocalyptic narrative about “What is to Come” as an adventus that exceeds the normal and surprising, as well as resistance to finding a new cosmic community model in an effort to live a new life in the new normal era. The order of discussion is as follows. First, Moltmann's apocalyptic thinking will be presented. Second, Žižek’s apocalyptic thinking will be presented. Third, the meeting points and relevance for apocalyptic resistance will be presented in the context of the current pandemic.